Modelling the baryon cycle in low-mass galaxy encounters: the case of NGC 4490 and NGC 4485 - Pearson, Sarah; Martínez-Delgado, David (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Discoveries of low-mass galaxy pairs and groups are increasing. Studies indicate that dwarf galaxy pairs are gas rich in the field and exhibit elevat
Gesehen am 08.02.2019